2016
DOI: 10.5897/ajb2016.15391
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol production from cassava peels using different microbial inoculants

Abstract: The potential of bioethanol production using different microbial inoculants for the simultaneous saccharification and fermentation of cassava peels from three cassava cultivars was investigated. Peels obtained from three cassava cultivars namely TME 0505, TME 419 and TME 4779, were washed, dried in a laboratory air oven dryer at 120°C for 3 h, ground into a fine texture and sieved with 1.5 µ nylon sieve. The sieved material was cultured using the following inoculant combinations: A = Rhizopus nigricans + Sacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The results of this experiment were also more significant than those of Adegunloye and Udenze (2017), who found that cocoyam peel fermented with A. niger and S. cerevisiae produced an ethanol yield of 6% at its highest. However, the value obtained in the present work was lower compared to the peak ethanol concentration of 41 % (v/v) and peak yield of 14.46 ± 2.08 g/cm 3 given by Chibuzor et al (2016) when CP cultivar TME 4779 was treated with Rhizopus nigricans, Spirogyra africana and S. cerevisiae, respectively.…”
Section: Agjsrcontrasting
confidence: 81%
See 1 more Smart Citation
“…The results of this experiment were also more significant than those of Adegunloye and Udenze (2017), who found that cocoyam peel fermented with A. niger and S. cerevisiae produced an ethanol yield of 6% at its highest. However, the value obtained in the present work was lower compared to the peak ethanol concentration of 41 % (v/v) and peak yield of 14.46 ± 2.08 g/cm 3 given by Chibuzor et al (2016) when CP cultivar TME 4779 was treated with Rhizopus nigricans, Spirogyra africana and S. cerevisiae, respectively.…”
Section: Agjsrcontrasting
confidence: 81%
“…Using S. cerevisiae to produce simple sugars from CP under controlled conditions will require process parameter optimization, which could increase bioethanol yield. This study led to the conclusion that CP might be used as a source of carbon energy for the yeast that is fermenting to produce ethanol (Chibuzor, Uyoh, & Igile, 2016). The selection of yeast for this study may have been influenced by its greater tolerance for acidic environments and low pH levels than other microbes, such as bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…BSG is interesting biomass with hydrolyzable fermentable sugars that can be converted to ethanol with different microorganisms through co-fermentation strategies (Rojas-Chamorro et al, 2020). Likewise, cassava peels, potato peels and millet husks with different microbial inoculants such as S. cerevisiae, Rhizopus nigricans, Aspergillus niger, Spirogyra africana showed great potential for bioethanol production (Chibuzor et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…There was previous research bioethanol production research using cassava peel as raw material. Different microbial inoculants such as Rhizopus nigricans, Spirogyra africana, Saccharomyces cerevisiae for the simultaneous saccharification and fermentation of cassava peels (Chibuzor et al, 2016). Production of bio-ethanol from cassava peels using Aspergillus niger and Saccharomyces cerevisiae (Adetunji et al, 2015) followed by research objectives.…”
Section: Introductionmentioning
confidence: 99%